2013
DOI: 10.1016/j.bandl.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Two action systems in the human brain

Abstract: The distinction between dorsal and ventral visual processing streams, first proposed by Ungerleider and Mishkin (1982) and later refined by Milner and Goodale (1995) has been elaborated substantially in recent years, spurred by two developments. The first was proposed in large part by Rizzolatti and Matelli (2003) and is a more detailed description of the multiple neural circuits connecting the frontal, temporal, and parietal cortices. Secondly, there are a number of behavioral observations that the classic “t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
315
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(345 citation statements)
references
References 96 publications
(132 reference statements)
27
315
1
2
Order By: Relevance
“…However, with a conventional subtraction method based on mass univariate analysis, it cannot be decided whether there is left IPL, which is consistent with the lesion cases of IMA (Buxbaum et al 2007;Binkofski and Buxbaum 2013). Notably, the observed accuracy for the cross-classification (43.1%) is significantly higher than chance (33%) but is still relatively low.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, with a conventional subtraction method based on mass univariate analysis, it cannot be decided whether there is left IPL, which is consistent with the lesion cases of IMA (Buxbaum et al 2007;Binkofski and Buxbaum 2013). Notably, the observed accuracy for the cross-classification (43.1%) is significantly higher than chance (33%) but is still relatively low.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies using anodal transcranial direct current stimulation (tDCS) showed that electrical stimulation of the left PPC improves the processing of gesture or imitation in healthy participants (Weiss et al 2013) and also in IMA patients (Bianchi et al 2015;Bolognini et al 2015), which further suggest the importance of left PPC for gesture processing. 15 Among the dorsal visual stream within the PPC, the dorso-dorsal pathway comprising the superior parietal lobule (SPL) and ventro-dorsal pathway, including the IPL, are distinct pathways (Rizzolatti and Matelli 2003;Binkofski and Buxbaum 2013). Online sensorimotor control with objects based on their perceptual attributes ("acting on") is mainly related to the SPL, whereas the stored knowledge of tool-use ("acting with") is 20 subserved by the IPL (Johnson and Grafton 2003;Brandi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our proposal of a dual route of affective perception [39], and related perspectives [50,[78][79][80], suggest that relatively independent detection and recognition routes underlie affective signal processing. These routes correspond to a dorsal and ventral division, respectively [69,81,82]. The first route comprises subcortical regions, such as the pulvinar and AMG as well as the dorsal stream and orbitofrontal cortex, and sustains early emotion processing, automatic action preparation and reflexive reactions.…”
Section: (D) Ventral and Dorsal Streammentioning
confidence: 99%
“…Recent evidence suggests that integration of known and visible properties of an object is carried out by a purported 'ventro-dorsal' sub-stream within the visual pathways model, with the left inferior parietal lobe (IPL) being the critical juncture where these object properties are combined (Rizzolatti & Matteli, 2003;Binkofski & Buxbaum, 2013;Vingerhoets, 2014).…”
Section: Introductionmentioning
confidence: 99%